2009
DOI: 10.1021/ac900278q
|View full text |Cite
|
Sign up to set email alerts
|

Hexose Rearrangements upon Fragmentation of N-Glycopeptides and Reductively Aminated N-Glycans

Abstract: Tandem mass spectrometry of glycans and glycoconjugates in protonated form is known to result in rearrangement reactions leading to internal residue loss. Here we studied the occurrence of hexose rearrangements in tandem mass spectrometry of N-glycopeptides and reductively aminated N-glycans by MALDI-TOF/TOF-MS/MS and ESI-ion trap-MS/MS. Fragmentation of proton adducts of oligomannosidic N-glycans of ribonuclease B that were labeled with 2-aminobenzamide and 2-aminobenzoic acid resulted in transfer of one to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 40 publications
4
48
0
1
Order By: Relevance
“…fecalis. These assignments suggest that the observed variation in the hexose branch in the initial MS 2 analysis may be the result of terminal sugar re-arrangement during MS, as previously described (40). Although this suggests the identical group I mass glycan to be less variable than originally thought, the inability of NMR to detect the Hex-HexNAc-[Hex]-HexNAc 3 -diNAcBac glycan suggests low abundance glycan variability may still exist and is currently under investigation.…”
Section: Discussionsupporting
confidence: 52%
“…fecalis. These assignments suggest that the observed variation in the hexose branch in the initial MS 2 analysis may be the result of terminal sugar re-arrangement during MS, as previously described (40). Although this suggests the identical group I mass glycan to be less variable than originally thought, the inability of NMR to detect the Hex-HexNAc-[Hex]-HexNAc 3 -diNAcBac glycan suggests low abundance glycan variability may still exist and is currently under investigation.…”
Section: Discussionsupporting
confidence: 52%
“…ternal saccharosamine residue (Shi et al, 1999) Interestingly, hexose rearrangements with loss of the penultimate GlcNAc residue, that is, the second GlcNAc counted from the labeled end, have been observed in MALDI-TOF/TOF-MS of oligomannosidic N-glycans labeled with 2AB and AA (Wuhrer, Koeleman, & Deelder, 2009) but not in MALDI-post-source decay (PSD)-TOF-MS of oligomannosidic N-glycans labeled with 4-aminobenzoic acid 2-(diethylamino)ethyl ester (Mo et al, 1998). Additional experiments are required to explain whether these observations are a result of the different physicochemical properties of the label or of the difference in energy deposition in the two MS-systems.…”
Section: A Reductively Aminated Glycansmentioning
confidence: 99%
“…However, the fragments indicated that fucose was linked to the first GlcNAc as well as to one of the mannoses. Proton adducts of fucosylated N-glycans are prone to fucose rearrangement, which gives rise to misleading fragments and therefore, the sodium adduct was selected for analysis by collision-induced decay (23,24). This yielded fragments unambiguously indicating the fucose to be linked to a mannose residue (Fig.…”
Section: Structural Characterization Of Chanterelle N-glycans By Massmentioning
confidence: 99%